Managing African commons in the context of Covid-19 challenges - Mapedza, Everisto D. (Ubiquity Press, Ltd., 2023)
The global Covid-19 pandemic is one of the major defining moments for development. In Africa, the syndemic, which the Global Landscape Forum refers to as a ‘synergy of epidemics’ impacted the continent. Whilst Covid-19 started as a health crisis, it has cut across all facets of life. The special issue initially aimed on discussing within this multifaceted crisis and drawing the implications for the common natural resources in Africa such as atmospheric commons (climate), land, water, forests, fisheries, pastoralism, urban and knowledge commons whilst also using a gender lens.